PENGARUH MEREK DAN NEGARA ASAL TERHADAP SIKAP KONSUMEN DALAM MEMILIH PRODUK HANDPHONE - Fransiskus, Yogi; Nasution, Armin Rahmansyah (JURNAL PLANS, 2017)
This research aims to determine the Influence of Brand and Country of Originto Consumer Attitude when Choosing Handphone Product at Erafone Medan Fair. Population in this research is 4210 persons. and sample is 98 persons. Sampling technique that use in this research is random sampling technique. Data analysis technique used is Multiple Linear Regression. Before we do the regression, first we need to test is the relationship between variables using classical assumption test. Then t test for parcial test and F test for simultaneous test, to know whether there is influence of brand to consumer attitude in choosing handphone product, influence of country of origin to consumer attitude in choosing handphone product, and influence of brand and country of origin simultaneous to consumer attitude in choosing handphone product. Based on research that conducted, found that brand and country of origin have positive effect to consumer attitude when choosing handphone product.Â Keywords: Brand, Country of Origin, Consumer Attitude